2005
DOI: 10.1111/j.1600-0447.2004.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial dysmorphology in Swedish schizophrenia patients

Abstract: The consistency of results across multiple studies supports the hypothesis that individuals with schizophrenia have increased rates of prenatal developmental disturbances. The presence of a dose-response type relationship between total dysmorphology score and patient/control status supports the importance of neurodevelopmental disturbance as a contributory cause of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…This atypical deletion does not include the HYDIN paralog by FISH (data not shown), and the head circumference of this individual is within the normal range. Our results are particularly of note in light of the recent finding of an association between 1q21.1 deletions and schizophrenia4,5, and the recognition of smaller head circumference and facial dysmorphic features among some schizophrenic individuals1618.…”
supporting
confidence: 62%
“…This atypical deletion does not include the HYDIN paralog by FISH (data not shown), and the head circumference of this individual is within the normal range. Our results are particularly of note in light of the recent finding of an association between 1q21.1 deletions and schizophrenia4,5, and the recognition of smaller head circumference and facial dysmorphic features among some schizophrenic individuals1618.…”
supporting
confidence: 62%
“…Although the Waldrop scale is currently the most widely used tool to assess dysmorphology in schizophrenia, its low sensitivity and lack of construct validity make it problematic. To address some of these deficits, a handful of studies have begun to incorporate anthropometric methods in order to generate quantitative descriptions of the head and face in schizophrenic individuals (Lane et al, 1997, Hennessey et al, 2004Kelly et al, 2005). Although results to date have been inconsistent, this approach is likely to yield a wealth of information about the nature of dysmorphology in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The total samples include 298 psychosis patients and 103 controls, with good representation throughout the adult age span of both sexes. The studies of Ismail et al (1998), Kelly et al (2005), and Lane et al (1997) have previously shown strong associations between MPA and schizophrenia, while the Nesvåg et al study (unpublished observations) constitutes preliminary results from ongoing research. If Lloyd et al's conclusions are correct and generalizable, one would predict increasing MPA rates with increasing age among both patients and controls and no difference in frequencies in MPA rates in schizophrenia versus control subjects of the same age.…”
mentioning
confidence: 96%
“…All controls were free of mental illness. More information can be obtained from the corresponding references (Lane et al 1997 ;Ismail et al 1998 ;Kelly et al 2005) and the first author of the Nesvåg et al study.…”
mentioning
confidence: 99%